A modified polyurethane adhesive for flexible copper clad laminate and preparation method thereof

Through the synergistic effect of the modified polyurethane adhesive and the flame retardant, the problem of insufficient performance of existing flexible copper clad adhesives is solved, and the effects of high mechanical properties, excellent flame retardant properties and good flexibility are achieved.

CN119775949APending Publication Date: 2025-04-08BLUE OCEAN & BLACK STONE TECH CO LTD (FUJIAN)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411951096.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The adhesive strength, flexibility and mechanical properties of existing flexible copper clad adhesives are insufficient, and the flame retardant properties are defective in the use of harmful gases.

Method used

Modified polyurethane adhesive is used to improve the mechanical properties and flame retardant properties of the adhesive by combining the combined hydroxy polyurethane and modified polyurethane, and using modified hexaphenoxycyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene as flame retardant.

Benefits of technology

It significantly improves the mechanical properties, flame retardant properties, bonding strength, flexibility and fold resistance of modified polyurethane adhesives for flexible copper clad plates, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005214894560000101
    Figure BDA0005214894560000101
Patent Text Reader

Abstract

The present application relates to the technical field of copper clad laminates, and in particular to a modified polyurethane adhesive for flexible copper clad laminates and a preparation method thereof. A modified polyurethane adhesive for flexible copper clad laminates comprises the following raw materials: 90-100 parts of hydroxyl-terminated polyurethane, 25-30 parts of modified polyurethane, 8-12 parts of flame retardant, 0.8-1.1 parts of coupling agent, 12-15 parts of curing agent, 1-1.2 parts of accelerator, and 25-30 parts of organic solvent. The modified polyurethane adhesive provided in the present application has significant advantages in improving flame retardancy, mechanical properties and bonding strength, and has good softness and folding resistance, and has important industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of copper clad laminates, and in particular to a modified polyurethane adhesive for flexible copper clad laminates and a preparation method thereof. Background Art

[0002] As electronic products develop towards miniaturization, lightness and high performance, flexible printed circuit boards are widely used in modern electronic devices due to their unique flexibility and thinness. As the basic material of flexible printed circuit boards, the performance of flexible copper clad laminates directly affects the quality of the final product.

[0003] Flexible copper clad laminate (FCCL) is a processing substrate material for flexible printed circuit boards. It is composed of a flexible insulating base film and a metal foil. A flexible copper clad laminate composed of three different materials, copper foil, film, and adhesive, is called a three-layer flexible copper clad laminate (referred to as "3L-FCCL"). Flexible copper clad laminates without adhesives are called two-layer flexible copper clad laminates (referred to as "2L-FCCL"). Currently, three-layer flexible copper clad laminates are the most widely used. They are usually made of polyimide film, copper foil, and adhesives through hot pressing. Adhesives are an important component of three-layer flexible copper clad laminates, which directly affect the product performance and quality of flexible copper clad laminates. The main adhesives used for flexible copper clad laminates are polyester adhesives, acrylic adhesives, epoxy or modified epoxy adhesives, polyimide adhesives, phenolic-butyral adhesives, etc. In the three-layer flexible copper clad laminate industry, adhesives are mainly divided into two categories: acrylic adhesives and epoxy adhesives. At present, most epoxy resins use bromine-containing epoxy resins and antimony compounds as flame retardants, which produce toxic gases that are harmful to the human body and the environment when burned. In addition, the bonding strength, flexibility and mechanical properties of adhesives need to be improved. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present application provides a modified polyurethane adhesive for a flexible copper-clad laminate and a preparation method thereof. The modified polyurethane adhesive for a flexible copper-clad laminate prepared in the present application has excellent mechanical properties, flame retardancy, peel strength, softness and folding resistance, and has broad application prospects. In addition, the preparation method of the present application has a simple process, is easy to control, and is conducive to industrial production.

[0005] In the first aspect, the present application provides a modified polyurethane adhesive for flexible copper clad laminates, adopting the following technical scheme: a modified polyurethane adhesive for flexible copper clad laminates, comprising the following preparation raw materials, measured by mass: 90-100 parts of terminal hydroxyl polyurethane, 25-30 parts of modified polyurethane, 8-12 parts of flame retardant, 0.8-1.1 parts of coupling agent, 12-15 parts of curing agent, 1-1.2 parts of accelerator, and 25-30 parts of organic solvent, wherein the flame retardant is prepared by mixing modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene.

[0006] By adopting the above technical scheme, the terminal hydroxyl polyurethane: as the main component of the adhesive, provides the basic structure and mechanical properties of the adhesive. Modified polyurethane: used in combination with the terminal hydroxyl polyurethane, further improves the bonding strength and flexibility of the adhesive. In addition, the introduction of the aminocarbamate oxime bond and the imine bond in the modified polyurethane in the cross-linked network gives the adhesive excellent self-healing and bonding strength. Flame retardant: prepared by mixing modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene. These flame retardants have excellent flame retardant properties and high thermal stability, and at the same time improve the flame retardant properties of the adhesive through synergistic effects. Coupling agent: used to improve the dispersibility of the flame retardant and its compatibility with other components. Curing agent: promotes the curing reaction of the adhesive and improves the mechanical properties and durability of the adhesive. Accelerator: accelerates the curing reaction so that the adhesive can reach the desired performance faster. Organic solvent: used to adjust the viscosity and fluidity of the adhesive for easy construction and curing. The result of the combined action of these components is the preparation of a modified polyurethane adhesive for flexible copper-clad laminates having excellent mechanical properties, flame retardancy, bonding strength, flexibility and folding resistance.

[0007] Preferably, the mass ratio of the modified hexaphenoxy cyclotriphosphazene to the modified hexa(4-aminophenoxy)cyclotriphosphazene is 4:2-4.

[0008] By adopting the above technical scheme, the flame retardant properties of the modified polyurethane adhesive are improved by compounding modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene, mainly through the synergistic flame retardant effect of organic phosphorus-nitrogen and nano-silica. At the same time, the modified hexaphenoxy cyclotriphosphazene and the modified hexa(4-aminophenoxy)cyclotriphosphazene are first modified by a silane coupling agent and then modified by nano-silica, which greatly improves their dispersibility and compatibility with other components, thereby improving the mechanical properties and flame retardant properties of the modified polyurethane adhesive. Hexaphenoxy cyclotriphosphazene is a phosphorus-nitrogen flame retardant with a unique PN hybrid structure, which gives it excellent flame retardant properties and high thermal stability, and has the characteristics of water resistance, oxidation resistance and low smoke generation during combustion. In addition, hexaphenoxy cyclotriphosphazene can be chemically grafted onto the surface of nano-silica particles after being modified by a silane coupling agent to prepare a new type of phosphorus-nitrogen nano flame retardant, and is used in modified polyurethane adhesives. Since silica nanoparticles can significantly improve the combustion properties of modified polyurethane adhesives such as heat release rate, organic phosphorus-nitrogen and nanoparticles have obvious synergistic flame retardant effects. The modified hexa(4-aminophenoxy)cyclotriphosphazene has an organic-inorganic hybrid structure with alternating single and double bonds of phosphorus and nitrogen, which can play a good synergistic flame retardant role; each phosphorus atom in the phosphazene molecule has two active PN bonds, which has good designability and can synthesize different phosphazene structures. The ring-crosslinked phosphazene compounds formed have various forms such as nanofibers, hollow spheres, and layered structures; due to the small size effect and high specific surface area of ​​nanomaterials, nanomaterials greatly improve the flame retardant properties of modified polyurethane adhesives. In summary, modified hexaphenoxycyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene significantly improve the flame retardant properties and mechanical properties of modified polyurethane adhesives through their unique structure and synergistic effect.

[0009] Preferably, the preparation method of the modified hexaphenoxy cyclotriphosphazene comprises the following steps: S31, according to the mass parts, 693 parts of hexaphenoxy cyclotriphosphazene and 124 parts of γ-(methacryloyloxy)propyltrimethoxysilane are added to 1200 parts of acetone, and heated to 75-80°C under nitrogen protection, and kept warm for 1-1.3 hours, then, 0.8 parts of azobisisoheptanenitrile are dissolved in 20 parts of acetone to obtain an azobisisoheptanenitrile solution, and the azobisisoheptanenitrile solution is slowly added dropwise within 1 hour, and then after reacting for 10-12 hours, the acetone is removed by rotary evaporation to obtain γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxy cyclotriphosphazene; S32. According to the mass proportion, nano-silica with a particle size of 20-30 nm is dried at 100-120°C for 6-8h, and then 350 parts of the dried nano-silica and 150 parts of γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxycyclotriphosphazene are added to 1500 parts of anhydrous ethanol. After stirring evenly, reflux the mixture at 78-82°C for 16-20h under nitrogen protection. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified hexaphenoxycyclotriphosphazene.

[0010] By adopting the above technical scheme, hexaphenoxy cyclotriphosphazene belongs to phosphorus-nitrogen flame retardant, which has a unique PN hybrid structure, giving it excellent flame retardant performance and high thermal stability, and has the characteristics of water resistance, oxidation resistance and low smoke generation during combustion. In addition, hexaphenoxy cyclotriphosphazene can be chemically grafted to the surface of nano-silica particles after modification by silane coupling agent to prepare a new type of phosphorus-nitrogen nano flame retardant, and applied to modified polyurethane adhesives. Since silica nanoparticles can significantly improve the combustion properties of adhesives such as heat release rate, organic phosphorus-nitrogen and nanoparticles have obvious synergistic flame retardant effects. It can significantly improve the mechanical properties and flame retardant properties of modified polyurethane adhesives.

[0011] Preferably, the preparation method of the modified hexa(4-aminophenoxy)cyclotriphosphazene comprises the following steps: S41, according to the mass parts, add 100 parts of hexachlorocyclotriphosphazene, 314 parts of acetaminophenol and 430 parts of potassium carbonate to 2500 parts of acetone and mix them evenly, then react at a temperature of 70-75° C. for 48-52 hours under nitrogen protection, then pour the reacted material into deionized water, stir, filter, collect the obtained solid, wash it with deionized water, n-hexane and ethanol in turn, place it in a vacuum drying oven at a temperature of 60-70° C. and dry it for 40-48 hours to obtain hexa(4-acetylaminophenoxy)cyclotriphosphazene; S42, according to the mass fraction; 51.8 parts of hexa(4-acetylaminophenoxy)cyclotriphosphazene, 500 parts of methanol and 130 parts of 43% sodium hydroxide aqueous solution are mixed uniformly, and the mixture is heated to 85-90° C. and reacted for 40-48 hours at a stirring rate of 100 rpm, and the reacted material is cooled to room temperature, filtered, and the solid is washed with deionized water and ethanol in turn, and then placed in a vacuum drying oven at a temperature of 68° C. and dried for 48 hours to obtain hexa(4-aminophenoxy)cyclotriphosphazene; S43, according to the mass parts, 52 parts of hexa(4-aminophenoxy)cyclotriphosphazene and 6.3 parts of γ-(methacryloyloxy)propyltrimethoxysilane are added to 200 parts of acetone, and the temperature is raised to 75-80°C under nitrogen protection, and the temperature is kept for 0.7-1h, then 0.3 parts of azobisisoheptanenitrile are dissolved in 10 parts of acetone to obtain an azobisisoheptanenitrile solution, and the azobisisoheptanenitrile solution is slowly added dropwise within 1h, and then after reacting for 10-12h, the acetone is removed by rotary evaporation to obtain γ-(methacryloyloxy)propyltrimethoxysilane-modified hexa(4-aminophenoxy)cyclotriphosphazene; S44. Dry the nano-silica with a particle size of 20-30 nm at 100-120°C for 6-8h according to the mass fraction, then add 180 parts of the dried nano-silica and 50 parts of γ-(methacryloyloxy)propyltrimethoxysilane-modified hexa(4-aminophenoxy)cyclotriphosphazene to 500 parts of anhydrous ethanol, stir evenly, and reflux at 78-82°C for 10-12h under nitrogen protection. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified hexa(4-aminophenoxy)cyclotriphosphazene.

[0012] By adopting the above technical scheme, the prepared modified hexa(4-aminophenoxy)cyclotriphosphazene has an organic-inorganic hybrid structure with alternating single and double bonds of phosphorus and nitrogen, which can play a good synergistic flame retardant role; each phosphorus atom in the phosphazene molecule has two active PN bonds, which has good designability and can synthesize different phosphazene structures. The ring-crosslinked phosphazene compounds formed have various forms such as nanofibers, hollow spheres, and layered structures; due to the small size effect and high specific surface area of ​​nanomaterials, nanomaterials greatly improve the flame retardant properties of modified polyurethane adhesives. At the same time, the modified hexa(4-aminophenoxy)cyclotriphosphazene is first modified by a silane coupling agent and then modified by nano-silicon dioxide, which greatly improves its dispersibility and compatibility with other components, thereby improving the mechanical properties and flame retardant properties of the modified polyurethane adhesive.

[0013] Preferably, the coupling agent is composed of γ-(methacryloyloxy)propyltrimethoxysilane and γ-mercaptopropyltriethoxysilane in a mass ratio of 3:1-3.

[0014] By adopting the above technical scheme, first, γ-(methacryloyloxy)propyltrimethoxysilane can react with the hydroxyl groups on the surface of inorganic materials (such as nano-silicon dioxide) to form a stable chemical bond, thereby improving the dispersibility and compatibility of inorganic materials in organic matrices. At the same time, it can also react chemically with organic materials (such as polyurethane) to form a cross-linked structure, thereby improving the mechanical properties and thermal stability of the material. Secondly, γ-mercaptopropyltriethoxysilane can react with the hydroxyl groups on the surface of inorganic materials to form a stable chemical bond, thereby improving the dispersibility and compatibility of inorganic materials in organic matrices. At the same time, it can also react chemically with organic materials (such as polyurethane) to form a cross-linked structure, thereby improving the mechanical properties and thermal stability of the material. Finally, the performance of the modified polyurethane adhesive is improved by compounding γ-(methacryloyloxy)propyltrimethoxysilane and γ-mercaptopropyltriethoxysilane, mainly through the synergistic effect between them. Both silane coupling agents can react chemically with inorganic and organic materials to form stable chemical bonds, thereby improving the mechanical properties and bonding strength of the material. At the same time, they can also improve the dispersibility and compatibility of inorganic materials in organic matrices, thereby further improving the comprehensive performance of modified polyurethane adhesives.

[0015] Preferably, the preparation method of the terminal hydroxyl polyurethane is as follows: 1 mol of polybutylene terephthalate and 1.5 mol of toluene diisocyanate are mixed, reacted at 85-90° C. for 2-2.5 hours to obtain a prepolymer, and 16 g of ethylene glycol is added and reacted for 1.8 hours to obtain the terminal hydroxyl polyurethane.

[0016] Preferably, the preparation method of the modified polyurethane comprises the following steps: S71. According to the mass fractions, 12.21 g of p-hydroxybenzaldehyde and 220 mL of anhydrous ethanol were mixed, the temperature was raised to 73° C., 9.91 g of 4,4'-diaminodiphenylmethane was added with stirring, and the mixture was kept warm for 3 h under a nitrogen atmosphere, and filtered to obtain a chain extender containing an imine bond; S72. Mix polytetramethylene glycol, isophorone diisocyanate, a chain extender containing an imine bond, dimethylglyoxime, dibutyltin dilaurate and tetrahydrofuran according to their mass fractions, and keep warm at 45-50°C for 1-2 hours; raise the temperature to 55-60°C, add hydroquinone and hydroxyethyl acrylate, continue to react for 4-5 hours, then distill under reduced pressure, keep warm at 45-50°C for 1-2 hours, add photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone, and stir ultrasonically for 10-30 minutes to obtain modified polyurethane.

[0017] By adopting the above technical scheme, the prepared modified polyurethane contains carbamate oxime ester bonds and imine bonds. The introduction of dynamic covalent bonds carbamate oxime ester bonds and imine bonds in the cross-linked network can effectively realize the cross-linked network structure of the adhesive, which can give the adhesive excellent self-healing properties and bonding strength.

[0018] Preferably, the dosage ratio of the polytetramethylene glycol, isophorone diisocyanate, chain extender containing an imine bond, dimethylglyoxime, dibutyltin dilaurate, tetrahydrofuran mixture, hydroquinone, hydroxyethyl acrylate and 2-hydroxy-2-methyl-1-phenyl-1-propanone is: 100g:0.45mol:50g:0.15mol:0.6g:130g:3g:0.3mol:10g.

[0019] Preferably, the organic solvent is ethyl acetate.

[0020] In a second aspect, the present application provides a method for preparing a modified polyurethane adhesive for a flexible copper clad laminate, using the following technical solution: As a general technical concept, the present application also provides a method for preparing the modified polyurethane adhesive for the flexible copper clad laminate, comprising the following steps: S101, adding an organic solvent into a reaction kettle according to the mass fraction, heating to 40-45° C. and stirring, adding hydroxyl-terminated polyurethane and modified polyurethane to completely dissolve; then adding a coupling agent and a flame retardant, stirring evenly, to obtain a mixture; S102. Add a curing agent and an accelerator to the mixture according to their weight proportions, stir evenly, and obtain a modified polyurethane adhesive for a flexible copper clad laminate.

[0021] In summary, the present application includes at least one of the following beneficial technical effects: 1. Excellent mechanical properties and flame retardant properties: By using modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene as flame retardants, and compounding terminal hydroxyl polyurethane and modified polyurethane, the mechanical properties and flame retardant properties of modified polyurethane adhesives have been significantly improved.

[0022] 2. Adhesive strength and flexibility: The introduction of dynamic covalent bonds, carbamate oxime bonds and imine bonds can effectively realize the cross-linked network structure of the adhesive, giving the adhesive excellent self-healing properties and adhesive strength. At the same time, the modified polyurethane adhesive has good flexibility and folding resistance.

[0023] 3. Synergistic flame retardant effect: Modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy) cyclotriphosphazene are chemically grafted onto the surface of nano-silica particles after being modified by silane coupling agent to form a new type of phosphorus-nitrogen-containing nano flame retardant. This synergistic flame retardant effect significantly improves the flame retardant properties of the adhesive.

[0024] 4. Broad application prospects: Because the modified polyurethane adhesive has excellent mechanical properties, flame retardant properties, bonding strength, softness and folding resistance, it has broad application prospects in the fields of flexible copper clad laminates. DETAILED DESCRIPTION

[0025] The embodiments of the present application will be described in detail below in conjunction with the examples, but those skilled in the art will understand that the following examples are only used to illustrate the present application and should not be considered to limit the scope of the present application. If the specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially. The curing agent is a polyurethane prepolymer purchased from Qingdao Huayuan Polymer Co., Ltd., model NX; the accelerator is purchased from Hangzhou Lin'an Weilan Auxiliary Co., Ltd., model WL-710.

[0026] In the following Examples and Preparation Examples, 1 part means 10 g.

[0027] Preparation Example 1 Preparation of modified hexaphenoxy cyclotriphosphazene The preparation method of modified hexaphenoxy cyclotriphosphazene comprises the following steps: S31. According to the mass fractions, 693 parts of hexaphenoxy cyclotriphosphazene and 124 parts of γ-(methacryloyloxy)propyltrimethoxysilane are added to 1200 parts of acetone, and the temperature is raised to 80° C. under nitrogen protection, and the temperature is kept for 1.2 hours. Then, 0.8 parts of azobisisoheptanenitrile are dissolved in 20 parts of acetone to obtain an azobisisoheptanenitrile solution, and the azobisisoheptanenitrile solution is slowly added dropwise within 1 hour. After reacting for 11 hours, the acetone is removed by rotary evaporation to obtain γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxy cyclotriphosphazene; S32. According to the mass proportion, nano-silica with an average particle size of 20 nanometers is dried at 120°C for 8 hours, and then 350 parts of the dried nano-silica and 150 parts of γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxycyclotriphosphazene are added to 1500 parts of anhydrous ethanol. After stirring evenly, reflux the mixture at 82°C for 17 hours under nitrogen protection. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified hexaphenoxycyclotriphosphazene.

[0028] Preparation Example 2 Preparation of modified hexa(4-aminophenoxy)cyclotriphosphazene The preparation method of modified hexa(4-aminophenoxy)cyclotriphosphazene comprises the following steps: S41. According to the mass fractions, 100 parts of hexachlorocyclotriphosphazene, 314 parts of acetaminophenol and 430 parts of potassium carbonate are added to 2500 parts of acetone and mixed evenly, and then reacted at a temperature of 73° C. for 50 hours under nitrogen protection, and then the reacted material is poured into deionized water, stirred, filtered, and the solid is collected and washed with deionized water, n-hexane and ethanol in turn, and then placed in a vacuum drying oven at a temperature of 66° C. for 45 hours to obtain hexa(4-acetylaminophenoxy)cyclotriphosphazene; S42, according to the mass fraction; 51.8 parts of hexa(4-acetylaminophenoxy)cyclotriphosphazene, 500 parts of methanol and 130 parts of a 43% sodium hydroxide aqueous solution were mixed uniformly, and the mixture was heated to 88° C. and reacted for 46 hours at a stirring rate of 100 rpm. The reacted material was cooled to room temperature, filtered, and the solid was washed with deionized water and ethanol in turn, and then placed in a vacuum drying oven at a temperature of 68° C. and dried for 48 hours to obtain hexa(4-aminophenoxy)cyclotriphosphazene; S43, according to the mass parts, 52 parts of hexa(4-aminophenoxy)cyclotriphosphazene and 6.3 parts of γ-(methacryloyloxy)propyltrimethoxysilane are added to 200 parts of acetone, and the temperature is raised to 78° C. under nitrogen protection, and the temperature is kept for 0.8 h, then 0.3 parts of azobisisoheptanenitrile is dissolved in 10 parts of acetone to obtain an azobisisoheptanenitrile solution, and the azobisisoheptanenitrile solution is slowly added dropwise within 1 h, and then after reacting for 11 h, the acetone is removed by rotary evaporation to obtain γ-(methacryloyloxy)propyltrimethoxysilane-modified hexa(4-aminophenoxy)cyclotriphosphazene; S44. According to the mass proportion, nano-silica with an average particle size of 20 nanometers is dried at 120°C for 6 hours, and then 180 parts of the dried nano-silica and 50 parts of γ-(methacryloyloxy)propyltrimethoxysilane-modified hexa(4-aminophenoxy)cyclotriphosphazene are added to 500 parts of anhydrous ethanol. After stirring evenly, reflux the mixture at 82°C for 10 hours under nitrogen protection. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified hexa(4-aminophenoxy)cyclotriphosphazene.

[0029] Preparation Example 3 Preparation of Hydroxyl-Terminated Polyurethane The preparation method of the terminal hydroxyl polyurethane is as follows: 1 mol of polybutylene terephthalate and 1.5 mol of toluene diisocyanate are mixed, reacted at 87° C. for 2.3 hours to obtain a prepolymer, and 16 g of ethylene glycol is added and reacted for 1.8 hours to obtain the terminal hydroxyl polyurethane.

[0030] Preparation Example 4 Preparation of modified polyurethane The preparation method of modified polyurethane comprises the following steps: S71. According to the mass fractions, 12.21 g of p-hydroxybenzaldehyde and 220 mL of anhydrous ethanol were mixed, the temperature was raised to 73° C., 9.91 g of 4,4'-diaminodiphenylmethane was added with stirring, and the mixture was kept warm for 3 h under a nitrogen atmosphere, and filtered to obtain a chain extender containing an imine bond; S72. Mix 100 g of polytetrahydrofuran ether diol, 0.45 mol of isophorone diisocyanate, 50 g of a chain extender containing an imine bond, 0.15 mol of dimethylglyoxime, 0.6 g of dibutyltin dilaurate and 130 g of tetrahydrofuran according to their mass fractions, and keep warm at 48°C for 1.2 h; raise the temperature to 58°C, add 3 g of hydroquinone and 0.3 mol of hydroxyethyl acrylate, continue the reaction for 4.5 h, then distill under reduced pressure, keep warm at 48°C for 1.2 h, add 10 g of a photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone, and stir ultrasonically for 20 min to obtain a modified polyurethane.

[0031] Example 1 A modified polyurethane adhesive for a flexible copper clad laminate comprises the following raw materials, measured by weight: 90 parts of hydroxyl-terminated polyurethane, 25 parts of modified polyurethane, 8 parts of flame retardant, 0.8 parts of coupling agent, 12 parts of curing agent, 1 part of accelerator, and 25 parts of ethyl acetate, wherein the flame retardant is prepared by mixing modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene in a weight ratio of 4:2, and the coupling agent is composed of γ-(methacryloyloxy)propyltrimethoxysilane and γ-mercaptopropyltriethoxysilane in a weight ratio of 3:1; The method for preparing the modified polyurethane adhesive for the flexible copper clad laminate comprises the following steps: S101. Add ethyl acetate to a reaction kettle according to the mass fraction, heat to 40° C. and stir, add hydroxyl-terminated polyurethane and modified polyurethane to completely dissolve; then add coupling agent and flame retardant, stir evenly, and obtain a mixture; S102. Add a curing agent and an accelerator to the mixture according to their weight proportions, stir evenly, and obtain a modified polyurethane adhesive for a flexible copper clad laminate.

[0032] Example 2 A modified polyurethane adhesive for a flexible copper clad laminate comprises the following raw materials, measured by weight: 100 parts of hydroxyl-terminated polyurethane, 30 parts of modified polyurethane, 12 parts of flame retardant, 1.1 parts of coupling agent, 15 parts of curing agent, 1.2 parts of accelerator, and 30 parts of ethyl acetate, wherein the flame retardant is prepared by mixing modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene in a weight ratio of 4:4, and the coupling agent is composed of γ-(methacryloyloxy)propyltrimethoxysilane and γ-mercaptopropyltriethoxysilane in a weight ratio of 3:3; The method for preparing the modified polyurethane adhesive for the flexible copper clad laminate comprises the following steps: S101. Add ethyl acetate to a reaction kettle according to the mass fraction, heat to 45° C. and stir, add hydroxyl-terminated polyurethane and modified polyurethane to completely dissolve; then add coupling agent and flame retardant, stir evenly, and obtain a mixture; S102. Add a curing agent and an accelerator to the mixture according to their weight proportions, stir evenly, and obtain a modified polyurethane adhesive for a flexible copper clad laminate.

[0033] Example 3 A modified polyurethane adhesive for a flexible copper clad laminate comprises the following raw materials, measured by weight: 95 parts of hydroxyl-terminated polyurethane, 28 parts of modified polyurethane, 10 parts of a flame retardant, 1 part of a coupling agent, 14 parts of a curing agent, 1.1 parts of an accelerator, and 28 parts of ethyl acetate, wherein the flame retardant is prepared by mixing modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene in a weight ratio of 4:3, and the coupling agent is composed of γ-(methacryloyloxy)propyltrimethoxysilane and γ-mercaptopropyltriethoxysilane in a weight ratio of 3:2; The method for preparing the modified polyurethane adhesive for the flexible copper clad laminate comprises the following steps: S101. Add ethyl acetate to a reaction kettle according to the mass fraction, heat to 43° C. and stir, add hydroxyl-terminated polyurethane and modified polyurethane to completely dissolve; then add coupling agent and flame retardant, stir evenly, and obtain a mixture; S102. Add a curing agent and an accelerator to the mixture according to their weight proportions, stir evenly, and obtain a modified polyurethane adhesive for a flexible copper clad laminate.

[0034] Comparative Example 1 The same as Example 3, except that: 123 parts of hydroxyl-terminated polyurethane and 0 parts of modified polyurethane.

[0035] Comparative Example 2 The same as Example 3, except that: the flame retardant is modified hexaphenoxy cyclotriphosphazene.

[0036] Comparative Example 3 The same as Example 3, except that: the flame retardant is modified hexa(4-aminophenoxy)cyclotriphosphazene.

[0037] Comparative Example 4 The same as Example 3, except that: the coupling agent is γ-(methacryloyloxy)propyltrimethoxysilane.

[0038] Comparative Example 5 The same as Example 3, except that: the coupling agent is γ-mercaptopropyltriethoxysilane.

[0039] Performance testing The modified polyurethane adhesive samples for flexible copper clad laminates prepared in the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 5 were respectively coated on a polyamide film with a thickness of 15 μm, and the coating thickness was controlled to be 20 μm. Subsequently, the samples were baked in an oven at 150°C for 5 minutes to form a semi-cured adhesive layer on the polyamide film. A 40 μm thick copper foil was pressed onto the adhesive layer, placed in a vulcanizer at 120°C for hot pressing for 2 minutes, and then cured at 165°C for 5 minutes to obtain a flexible copper clad laminate. The following tests were performed, and the results are shown in Table 1.

[0040] The peel strength is tested according to the peel strength IPC-TM-6502.4.9 method for flexible circuits; The rebound force can quantitatively reflect the softness of the flexible copper clad laminate. The smaller the rebound force, the softer the flexible copper clad laminate. Test according to the following method: ① Set the spacing of the compression fixture of the material testing machine to 30mm before compression and 1mm after compression; ②Cut a sample with a length of 120mm and a width of 15mm, place the sample vertically in the upper and lower compression fixtures, ensure that the lines at both ends are parallel and coincide with the outer ports of the fixtures, then tighten the fixtures to secure the sample; ③ Compress the sample at a running speed of 50 mm / min, hold the load for 30 seconds after the compression run, record the maximum force and holding force during the process, and take the average value as the rebound force.

[0041] Folding resistance is tested according to JIS C-6471 standard; Flame retardant properties (limiting oxygen index): tested according to GB / T2406.2-2009 standard, the limiting oxygen index of the sample was measured by an oxygen index meter; the sample preparation method was as follows: the modified polyurethane adhesive for flexible copper clad laminate prepared in the above-mentioned Examples 1-3 and Comparative Examples 1-5 was sampled, poured into a mold, and the sample thickness was ensured to be uniform (3 mm), placed in a ventilated place to dry naturally for 12 hours, and then dried in an oven at 150° C. for 10 minutes to obtain a solid sample, the sample was taken out of the mold, placed in a dryer, and the humidity was balanced for 24 hours, and then cut into a standard size suitable for mechanical property testing (100 mm×10 mm test piece); Elongation at break: According to the standard described in ASTM D5034, the sample was tested using UTM equipment at a tensile speed of 500 mm / min. The sample preparation method is as follows: the modified polyurethane adhesive for flexible copper clad laminate prepared in the above-mentioned Examples 1-3 and Comparative Examples 1-5 was sampled, poured into a mold, and the sample thickness was ensured to be uniform (3 mm), placed in a ventilated place to dry naturally for 12 hours, and then dried in an oven at 150°C for 10 minutes to obtain a solid sample, the sample was taken out of the mold, placed in a dryer, and the humidity was balanced for 24 hours, and then cut into a standard size suitable for mechanical property testing (100 mm × 10 mm test piece).

[0042] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The modified polyurethane adhesive for flexible copper clad laminates prepared in Examples 1 to 3 has excellent mechanical properties, flame retardancy, peel strength, flexibility and folding resistance, and has broad application prospects.

[0043] 2) The comparative analysis of the performance of the modified polyurethane adhesive for flexible copper clad laminates prepared in Example 3 and Comparative Example 1 shows that the added modified polyurethane contains carbamate oxime ester bonds and imine bonds, and the introduction of dynamic covalent bonds carbamate oxime ester bonds and imine bonds in the cross-linked network can effectively realize the cross-linked network structure of the adhesive, and can give the adhesive excellent self-healing properties and bonding strength.

[0044] 3) The performance comparison analysis of the modified polyurethane adhesive for flexible copper clad laminate prepared in Example 3 and Comparative Examples 2-3 shows that the flame retardant is prepared by mixing modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene in a mass ratio of 4:3, mainly through the synergistic flame retardant effect of organic phosphorus-nitrogen and nano-silicon dioxide. At the same time, the modified hexaphenoxy cyclotriphosphazene and the modified hexa(4-aminophenoxy)cyclotriphosphazene are first modified by a silane coupling agent and then modified by nano-silicon dioxide, which greatly improves their dispersibility and compatibility with other components, thereby improving the mechanical properties and flame retardant properties of the modified polyurethane adhesive. The unique structure and synergistic effect of modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene significantly improve the mechanical properties and flame retardant properties of the modified polyurethane adhesive.

[0045] 4) The performance comparison analysis of the modified polyurethane adhesive for flexible copper clad laminate prepared in Example 3 and Comparative Examples 4-5 shows that the coupling agent is composed of γ-(methacryloyloxy)propyltrimethoxysilane and γ-mercaptopropyltriethoxysilane in a mass ratio of 3:2. By utilizing the synergistic effect between them, these two silane coupling agents can chemically react with inorganic materials and organic materials to form stable chemical bonds, thereby improving the mechanical properties and bonding strength of the modified polyurethane adhesive. At the same time, they can also improve the dispersibility and compatibility of inorganic materials in organic matrices, thereby further improving the comprehensive performance of the modified polyurethane adhesive.

[0046] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.

Claims

1. A modified polyurethane adhesive for a flexible copper-clad laminate, characterized in that: The preparation raw materials include, by weight: 90-100 parts of terminal hydroxyl polyurethane, 25-30 parts of modified polyurethane, 8-12 parts of flame retardant, 0.8-1.1 parts of coupling agent, 12-15 parts of curing agent, 1-1.2 parts of accelerator and 25-30 parts of organic solvent, wherein the flame retardant is prepared by mixing modified hexaphenoxy cyclotriphosphazene and modified hexa(4-aminophenoxy)cyclotriphosphazene.

2. A modified polyurethane adhesive for a flexible copper clad laminate according to claim 1, characterized in that: The mass ratio of the modified hexaphenoxy cyclotriphosphazene to the modified hexa(4-aminophenoxy)cyclotriphosphazene is 4:2-4.

3. The modified polyurethane adhesive for flexible copper clad laminate according to claim 1, characterized in that: The preparation method of the modified hexaphenoxy cyclotriphosphazene comprises the following steps: S31. According to the mass fractions, 693 parts of hexaphenoxy cyclotriphosphazene and 124 parts of γ-(methacryloyloxy)propyltrimethoxysilane are added to 1200 parts of acetone, and the mixture is heated to 75-80°C under nitrogen protection, and kept warm for 1-1.3 hours. Then, 0.8 parts of azobisisoheptanenitrile are dissolved in 20 parts of acetone to obtain an azobisisoheptanenitrile solution. The azobisisoheptanenitrile solution is slowly added dropwise within 1 hour, and then the mixture is reacted for 10-12 hours, and the acetone is removed by rotary evaporation to obtain γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxy cyclotriphosphazene. S32. Dry nano-silica with a particle size of 20-30 nanometers at 100-120°C for 6-8 hours according to the mass fraction, then add 350 parts of the dried nano-silica and 150 parts of γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxycyclotriphosphazene to 1500 parts of anhydrous ethanol, stir evenly, and reflux at 78-82°C for 16-20 hours under nitrogen protection. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified hexaphenoxycyclotriphosphazene.

4. The modified polyurethane adhesive for flexible copper clad laminate according to claim 1, characterized in that: The preparation method of the modified hexa(4-aminophenoxy)cyclotriphosphazene comprises the following steps: S41, according to the mass parts, add 100 parts of hexachlorocyclotriphosphazene, 314 parts of acetaminophenol and 430 parts of potassium carbonate to 2500 parts of acetone and mix them evenly, then react at a temperature of 70-75° C. for 48-52 hours under nitrogen protection, then pour the reacted material into deionized water, stir, filter, collect the obtained solid, wash it with deionized water, n-hexane and ethanol in turn, place it in a vacuum drying oven at a temperature of 60-70° C. and dry it for 40-48 hours to obtain hexa(4-acetylaminophenoxy)cyclotriphosphazene; S42, according to the mass fraction; 51.8 parts of hexa(4-acetylaminophenoxy)cyclotriphosphazene, 500 parts of methanol and 130 parts of 43% sodium hydroxide aqueous solution are mixed uniformly, and the mixture is heated to 85-90° C. and reacted for 40-48 hours at a stirring rate of 100 rpm, and the reacted material is cooled to room temperature, filtered, and the solid is washed with deionized water and ethanol in turn, and then placed in a vacuum drying oven at a temperature of 68° C. and dried for 48 hours to obtain hexa(4-aminophenoxy)cyclotriphosphazene; S43, according to the mass parts, 52 parts of hexa(4-aminophenoxy)cyclotriphosphazene and 6.3 parts of γ-(methacryloyloxy)propyltrimethoxysilane are added to 200 parts of acetone, and heated to 75-80°C under nitrogen protection, and kept warm for 0.7-1h, then, 0.3 parts of azobisisoheptanenitrile are dissolved in 10 parts of acetone to obtain an azobisisoheptanenitrile solution, and the azobisisoheptanenitrile solution is slowly added dropwise within 1h, and then after reacting for 10-12h, the acetone is removed by rotary evaporation to obtain γ-(methacryloyloxy)propyltrimethoxysilane-modified hexa(4-aminophenoxy)cyclotriphosphazene; S44. Dry nano-silica with a particle size of 20-30 nanometers at 100-120°C for 6-8 hours according to the mass fraction, then add 180 parts of the dried nano-silica and 50 parts of γ-(methacryloyloxy)propyltrimethoxysilane-modified hexa(4-aminophenoxy)cyclotriphosphazene to 500 parts of anhydrous ethanol, stir evenly, and reflux at 78-82°C for 10-12 hours under nitrogen protection. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified hexa(4-aminophenoxy)cyclotriphosphazene.

5. The modified polyurethane adhesive for flexible copper clad laminate according to claim 1, characterized in that: The coupling agent is composed of γ-(methacryloyloxy)propyltrimethoxysilane and γ-mercaptopropyltriethoxysilane in a mass ratio of 3:1-3.

6. The modified polyurethane adhesive for flexible copper clad laminate according to claim 1, characterized in that: The preparation method of the terminal hydroxyl polyurethane is as follows: 1 mol of polybutylene terephthalate and 1.5 mol of toluene diisocyanate are mixed, reacted at 85-90° C. for 2-2.5 hours to obtain a prepolymer, and then 16 g of ethylene glycol is added and reacted for 1.8 hours to obtain the terminal hydroxyl polyurethane.

7. The modified polyurethane adhesive for flexible copper clad laminate according to claim 1, characterized in that: The preparation method of the modified polyurethane comprises the following steps: S71. According to the mass fractions, 12.21 g of p-hydroxybenzaldehyde and 220 mL of anhydrous ethanol were mixed, the temperature was raised to 73° C., 9.91 g of 4,4'-diaminodiphenylmethane was added with stirring, and the mixture was kept warm for 3 h under a nitrogen atmosphere, and filtered to obtain a chain extender containing an imine bond; S72. Mix polytetramethylene glycol, isophorone diisocyanate, a chain extender containing an imine bond, dimethylglyoxime, dibutyltin dilaurate and tetrahydrofuran according to their mass fractions, and keep warm at 45-50°C for 1-2 hours; raise the temperature to 55-60°C, add hydroquinone and hydroxyethyl acrylate, continue to react for 4-5 hours, then distill under reduced pressure, keep warm at 45-50°C for 1-2 hours, add photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone, and stir ultrasonically for 10-30 minutes to obtain modified polyurethane.

8. A modified polyurethane adhesive for flexible copper clad laminate according to claim 7, characterized in that: The dosage ratio of the polytetramethylene glycol, isophorone diisocyanate, chain extender containing imine bond, dimethylglyoxime, dibutyltin dilaurate, tetrahydrofuran mixture, hydroquinone, hydroxyethyl acrylate and 2-hydroxy-2-methyl-1-phenyl-1-propanone is: 100g:0.45mol:50g:0.15mol:0.6g:130g:3g:0.3mol:10g.

9. The modified polyurethane adhesive for flexible copper clad laminate according to claim 1, characterized in that: The organic solvent is ethyl acetate.

10. A method for preparing a modified polyurethane adhesive for a flexible copper clad laminate as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: S101, adding an organic solvent into a reaction kettle according to the mass fraction, heating to 40-45° C. and stirring, adding hydroxyl-terminated polyurethane and modified polyurethane to completely dissolve; then adding a coupling agent and a flame retardant, stirring evenly, to obtain a mixture; S102. Add a curing agent and an accelerator to the mixture according to their weight proportions, stir evenly, and obtain a modified polyurethane adhesive for a flexible copper clad laminate.